The Dayak Selako Shamans Oral Tradition: Intermediary Between People, Culture And Religion - Kristianus Kristianus (Al-Albab, 2021)
The Dayak Shamans of Western Kalimantan of Borneo mediate between people and the Makhluk halus or invisible beings. The Makhluk halus who have their own well-defined roles, live in the sky, earth, water and other places, with similar needs as the humans, and the relations between humans and spirits in the context of traditional beliefs are inseparable. Interestingly, these beliefs are common to both Dayak Selako Shamanism and Kalimantan Islam. The Malay oral tradition has a major influence on the Dayak Selako culture in Western Kalimantan. In fact, both ethnic groups had originated historically from the same roots, but later separated by Islam and Christianity. Thus, irrespective of their affiliations to the major religions of Christianity and Islam, the Dayak Selako Shamanism and the Islamic spiritual healing practiced in Western Kalimantan follow the same oral tradition when conducting spiritual communication and shamanic healing.  For the Malays, communication with the spiritual world begins with the recital of the Islamic verses, forming an essential part of the the Malay identity. Interestingly, the Dayak Selako Christians too use the same verses. We argue that the Dayak Selako Shaman is not only an intermediary between the Dayaks and their spirits,  but also between the Dayak, Islam and Christianit religions. The mutual values of oral tradition in shamanism’s of the Dayak Selako and Malays have created a societal structure based on the natural cycle and life pattern.